BH3‐only proteins are part of a regulatory network that control the sustained signalling of the unfolded protein response sensor IRE1α. (15th September 2021) - Rodriguez, Diego A; Zamorano, Sebastian; Lisbona, Fernanda; Rojas‐Rivera, Diego; Urra, Hery; Cubillos‐Ruiz, Juan R; Armisen, Ricardo; Henriquez, Daniel R; Cheng, Emily H; Letek, Michal; Vaisar, Tomas; Irrazabal, Thergiory; et al.
Abstract :